(untitled) (Research, Society and Development, 2021)
The present article carried out a technical analysis on an area declared of conflicts for the use of water resources, in the hydrographic basin of Quatis stream, located in the municipality of Itueta, Minas Gerais, and had as main objective to analyze the conflict for the use of water identified in the place. The research was based on the Conflict Analysis for Water Use (ACUA) document 01/2019, provided by the Mineiro Institute of Water Management (IGAM), with information related to users granted and of insignificant uses, flows from the basin, relationships demand x availability, and land use and occupation map. The results obtained by ACUA returned water deficit values ​​in the demand x availability ratio, in addition to being supported by the map of land use and occupation with uses mainly aimed at irrigation; and the solutions found for the conflict were related to the establishment of a Local Management Commission and the elaboration of the water allocation term for collective award. Finally, in addition to the solutions aimed at minimizing or resolving the conflict, other initiatives related to environmental projects to increase the region’s water potential were indicated.